Analisis Pemanfaatan INLISLite dalam Pengolahan Bahan Pustaka di Dinas Perpustakaan dan Kearsipan Kabupaten Tanah Datar - Yohanna, Mutia; Marlini, Marlini; Erlianti, Gustina (Lembaga Yasin AlSys, 2026)
INLISLite is one of the library automation systems widely used in Indonesia to improve the efficiency of library materials processing and to support modern library services; therefore, its use plays an important role in enhancing the accuracy of collection data and the speed of service delivery. This study aimed to analyze the use of INLISLite in library materials processing at the Library and Archives Office of Tanah Datar Regency based on a literature review. The study employed a literature review of two relevant journal articles published between 2021 and 2023, using content analysis to identify patterns of use, constraints, and the effectiveness of INLISLite in collection management. The findings indicate that INLISLite can improve the efficiency of collection processing, circulation services, and membership management in a faster and more organized manner. The main constraints identified include limited system updates, network integration issues, and librarians’ technical capacity, while training implementation and institutional support were shown to facilitate the optimization of system use. Overall, the study concludes that INLISLite contributes significantly to improving the quality of library materials processing and library services at the Library and Archives Office of Tanah Datar Regency, and it underscores the importance of strengthening technological infrastructure and enhancing human resource competencies to ensure the sustainability of optimal library automation system use.